KARAKTERISTIK HABITAT dan POLA DISTRIBUSI KULIM (Scorodocarpus borneensis Becc.) di SEPANJANG JALUR UTAMA PATROLI TAMAN HUTAN RAYA SULTAN SYARIF HASYIM PROVINSI RIAU - Dina Rina Rosinta; Defri Yoza; Evi Sribudiani (Fakultas Pertanian, Universitas Riau, 2019)
Kulim is a multipurpose tree species (MPTS), which all parts of its tree has high economy value. Its wood that is widely used by the community and causing high exploitation for this species. The purpose of this study was determine characteristic of habitat and distribution pattern of kulim (Scorodocarpus borneensis Becc.) along the main patrol line of Taman Hutan Raya Sultan Syarif Hasyim in Riau Province. Methode used in this study was survey method using vegetation analysis. In this research this method was combination of transect method and line method. The result of this research was kulim (Scorodocarpus borneensis Becc.) that was grown along the main patrol line of the Taman Hutan Raya Sultan Syarif Hasyim as follows the seed grows in yellowish brown sandy soil; an average water content of 6,1 with a pH of 5,89 (slightly acidic); average temperatur average of 25,71 and average humidity of 71,46. The distribution pattern of kulim along the main patrol line of Taman Hutan Raya Sultan Syarif Hasyim, which has a clumped distribution pattern.